St. Vincent and the Grenadines : 2006 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the 2006 Article IV Consultation on St. Vincent and the Grenadines highlights economic prospects and the fiscal situation. St. Vincent and the Grenadines is a small, open economy that has increasingly relied on its tourism sector. The export-oriented services sector accounts for about three-fourth of total value added, and the import content of both domestic consumption and investment is high. Despite ongoing efforts to enhance statistical databases in St. Vincent and the Grenadines, weaknesses remain in terms of coverage, timeliness, and dissemination of statistical data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet